Space Weathering Induced Via Microparticle Impacts: 1. Modeling of Impact Velocities and Flux of Micrometeoroids From Cometary, Asteroidal, and Interstellar Origin in the Main Asteroid Belt and the Near‐Earth Environment. Issue 4 (29th April 2019) - Altobelli, N.; Fiege, K.; Carry, B.; Soja, R.; Guglielmino, M.; Trieloff, M.; Orlando, T. M.; Srama, R.
Abstract: The processes of alteration of airless bodies exposed to the space environment are referred to be as "space weathering." Multiple agents contribute generally to space weathering, to an extent that depends on the specific location of the surface within the solar system. Typical space weathering agents encountered in the solar system are solar radiation, solar wind and cosmic rays, magnetospheric plasma (e.g., at Jupiter or Saturn), and cosmic dust. The effect of space weathering is generally assessed by measuring the surfaces optical properties, for example, by near‐infrared spectroscopy. The alteration of the surfaces is due to a cumulative effect over time of all agents. We investigate in this paper the contribution of micrometeoroid (dust) bombardment on different asteroids, by using the Interplanetary Micrometeoroid Environment Model for the interplanetary dust populations and a simplified model of interstellar dust dynamics. We quantify, for different representative asteroids (main belt and Near Earth Objects [NEOs]), the particle cumulative flux, mass flux, impact velocity, and the kinetic impact energy deposited. This work is primarily intended to support laboratory work investigating the effect of energy deposition onto sample surfaces, as well as astronomical observations of optical properties of asteroid surfaces. Plain Language Summary: This paper explores the impact speed, mass flux, and kinetic energy flux of interplanetary and interstellar micrometeoroids on near‐earth and main belt asteroids from different dynamical families. This paper aims at providing constraints to current and future experimental work to understand the space weathering of asteroids surfaces induced by dust impacts.The simulations are performed using the latest version of the micrometeoroid environment model of the European Space Agency (Interplanetary Micrometeoroid Environment Model). We find that for all asteroids studied, the dust impactors deposit orders of magnitude less energy on the asteroid surfaces compared to the solar radiations but their contribution is comparable to that of heavy solar wind ions and electrons. We find that large cometary grains provide most of the mass flux delivered to asteroids surfaces, independently of the asteroids orbital elements, suggesting that dust bombardment is unlikely to play a significant role in driving the observed spectral trends among the different asteroids. While surface gardening by dust bombardment may, in turn, expose fresh material from the asteroid's surface, the required interplanetary dust population mass flux seems too low to efficiently counterbalance the surface weathering due to solar wind implantation. Key Points: This paper presents the modeling of micrometeoroid impacts on main belt and near-Earth asteroids The contribution of cometary, asteroidal, and interstellar dust as space weathering agents is evaluated